The Influence of Quality of Productive Assets, Liquidity, and Profitability on Risk Management Disclosure with Company Size as a Moderating Variable in Banking Companies Listed on the Indonesia Stock Exchange - Rizki Marbun, Sri; Erwin, Keulana; Syarif, Firman (International Journal of Economics, Management and Accounting (IJEMA), 2023)
The research investigates the impact of productive asset quality, liquidity, and profitability on risk management disclosure in Indonesian banking companies listed on the Indonesia Stock Exchange from 2017 to 2022. Utilizing Eviews 10 software, the analysis employs panel data regression, descriptive statistical tests, multiple linear regression, and moderation analysis. The sample comprises 22 banking companies, selected through random sampling, using secondary data. Findings indicate a significantly negative relationship between productive asset quality and risk management disclosure. Moreover, firm size amplifies this negative impact. In contrast, liquidity and profitability do not significantly influence risk management disclosure. Notably, firm size diminishes the significance of liquidity and profitability in the context of Indonesian banking companies. These results offer insights into the intricate dynamics of risk management disclosure and highlight the nuanced role of firm size in shaping these relationships.